PENGARUH BEBAN KERJA DAN KOMPETENSI TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH STRES KERJA (Studi Pada Pegawai Negeri Sipil Dinas Koperasi Usaha Kecil Dan Menengah Provinsi Daerah Istimewa Yogyakarta) - Ridha Andaru Jehan Pramesthi; Anis Siti Hartati; Istiana Rahatmawati (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2020)
This research aims to analyze the direct influence of workload on performance and competence of employees as well as the indirect influence of workload on performance and competence of employees are mediated by workstress. The Independent variables used in this study workload and competence, whereas the depedent variable was employee performance and the mediating variable is. The population in this study are employees of Dinas Koperasi Usaha Kecil dan Menengah Provinsi Daerah Istimewa Yogyakarta-totalling 41 people, while the research method used is the sampling of saturated. The analysis in this study is the path analysis. Hypothesis test results in this study is there is direct a influence of workload on performance of employees, there is a direct influence on performance of competence of employees, there is a direct influence of workload on performance employees with workstress as an mediating variable, and there is the influence of indirect competence on performance of employees with workstress as an mediating variable.